Designing a Media Literacy Training Curriculum Framework for Junior High School Teachers - Fadlillah, Ahmad Fajar; Ali, Mohammad; Hernawan, Asep Herry; Riyana, Cepi (JTP - Jurnal Teknologi Pendidikan, 2023)
Being capable of media literacy is an important competence in the contemporary era characterized by widespread digitalization. Teachers play a vital role in integrating learning and imparting it in schools. However, due to the absence of media literacy training, their level of media literacy remains low. It necessitates a solution involving the creation of a training program by designing its curriculum beforehand. This study attempts to design a curriculum framework for media literacy training for teachers. The participants were junior high school teachers in West Java, with a total sample size of 381 teachers who used purposive sampling techniques. A design research method has been used to produce a prototype for research purposes. Research procedure refers to the three decisions that determine the design outcome, covering procedure design, problem analysis and solution design Data collected with questionnaires given to teachers and it has been analyzed using descriptive statistics with SPSS software 26. Results of this study provide a curriculum framework for media literacy training for junior high school teachers in West Java, including objectives, content, methods, and assessment. Its current training curriculum framework serves as a valuable reference point for enhancing the media literacy competence of teachers.